Elective transfemoral amputation and simultaneous implantation of a transcutaneous osseointegrated prosthesis stem as salvage treatment after knee joint arthrodesis with poor function: A case report - Krause, Katharina; Richter, Katherina; Beyer, Thomas; Aschoff, Horst Heinrich; Fischer, Dagmar-Christiane; Mittlmeier, Thomas (Frontiers in Surgery, 2022)
Background: Surgical reconstruction of anterior cruciate ligament ruptures is a well established procedure and although it is for the vast majority of patients without severe complications, total knee joint arthroplasty, arthrodesis of the knee and finally transfemoral amputation have to be considered in the worst case. The case: We report on a patient presenting with a 13-year history of recurrent failure after anterior cruciate ligament reconstruction. She claimed on a severely impaired mobility secondary to a knee joint arthrodesis via an Ilizarov circular frame two years ago and chronic immobilizing pain making a permanent medication with opioids necessary. She was aware of the therapeutic options and asked for transfemoral amputation and concomitant supply with a transcutaneous osseointegrated prosthesis system (TOPS). Procedures: After careful evaluation and clinical work-up the indication for transfemoral amputation and concomitant implantation of the prosthetic stem into the femoral cavity was secured. Six weeks afterwards, creation of the stoma for coupling of the artificial limb and onset of physiotherapy, balance and gait training were scheduled. 12 weeks after the index procedure, full weight-bearing and walking without crutches was allowed. This sequence of events was paralleled by a series of pre-defined examinations, i.e. questionnaires and mobility scores addressing the situation of transfemoral amputees together with standardized clinical gait analysis. The latter was performed prior to surgery and 6, 9 and 18 months after the index procedure. Outcome: Already at time of the index procedure opioids could be tapered to zero and the patient quickly restored her walking abilities during the rehabilitation period. Clinical gait analysis confirmed the restorage of bilateral symmetry by mutual approximation of kinematic and kinetic to a standard gait pattern. Conclusion: The outcome of our patient strengthens the therapeutic potential of an unilateral transfemoral amputation in combination with TOPS. Nevertheless, long term follow-up is necessary to detect future complications of this approach.